The Tindims and the Ten Green Bottles - Sally Gardner (Britain Head Of Zeus Ltd, 2021)
In their third adventure Ethel B Dina, who looks after the fish hospital and loves to sing, needs ten green, glass bottles to complete her musical Bottleramma. But she is surrounded by too many plastic bottles which do not make music. Join the Tindims in their glass bottle hunt and meet the Tindims explorer, Tiddledum.
Keywords: Mystery -- Mystery; Adventure -- Adventure